From Energy to Information: Green Knowledge Production Function in Fragile Five Economies - Gülcü, Yunus; Özek, Yavuz; Bayat, Tayfur; Çanakçı, Burak (International Journal of Energy Economics and Policy, 2026)
Climate change and sustainable development goals make green energy (the development of environmentally related technologies) the main determinant of economic growth in the Fragile Five economies. In this study, the determinants of green innovation in the Fragile Five economies (Brazil, India, Indonesia, South Africa, and Turkey) during the period 2002–2020 are examined through panel data analysis. The empirical findings show that in the short run, increases in output encourage demand-driven innovation. In the long run, however, fixed capital investments, the stringency of environmental policies, and the level of human capital are indicated to be effective on green innovation. While in India, income growth and fixed capital investments feed innovation, in the Turkish economy, energy efficiency and renewable energy investments provide support. In Indonesia and South Africa, human capital strengthens the capacity for knowledge absorption and supports innovation. In Brazil, on the other hand, due to income growth being directed towards traditional energy-intensive sectors, the green innovation process slows down. According to the empirical findings, the stringency of environmental policies may suppress green innovation in the short term by increasing compliance costs, but in the long term, in line with the Porter hypothesis, it may stimulate green innovation. For these reasons, in the Fragile Five economies, it is necessary to direct physical capital toward green technologies through green financing instruments and to reduce firms’ compliance costs with predictable environmental policies.